Using Endoscopic Optical Coherence Tomography to Detect and Treat Early-Stage Pancreatic Cancers - Lu, Lanchun; Hu, Zhilin; Frankel, Wendy; Shen, Rulong; Chen, Wei; Pan, Xueliang; Grecula, John C.; Bloomston, Mark P.; Dillhoff, Mary E. (Frontiers in Oncology, 2021)
We developed a novel technology capable of detecting early-stage pancreatic cancers using high-resolution 3-dimensional endoscopic optical coherence tomography (Endo-OCT), and treating them using high dose rate brachytherapy (HDR) under the Endo-OCT image guidance. This technology integrates our custom-built ultra-high resolution endoscopic 3-dimensional OCT diagnostic imaging device with a commercial high dose rate brachytherapy system (HDR), resulting in a compact, portable, easy-to-operate, and low-cost Endo-OCT image-guided high dose rate brachytherapy (OCT-IGHDR) system. The system has the dual functions of diagnosis and treatment that can precisely detect and measure the location and size of the early-stage pancreatic cancer or premalignant lesions and then treat them from the inside of the pancreatic duct with an accurate, effective, and focused dose while greatly reducing the radiation toxicity to the neighboring tissues and organs. This minimally-invasive treatment technology could avoid the potential complications from surgery and reduces the high operation cost. This technology could also be applied to treat diseases of the esophagus, rectum, bronchus, and other aerodigestive organs that are suitable for use with an endoscopic device. In this article, we describe the concept of this innovative technology and the preliminary experiments that could demonstrate the concept by using this homemade Endo-OCT machine to image the pancreatic duct for diagnosis of early-stage pancreatic cancer or premalignant lesions and to perform Endo-OCT image-guided brachytherapy. The clinical trial results and the progress of this research project will be presented in future manuscripts.